User-Centered Smart Environments: Advanced Research on the Integration of User Preferences and Artificial Intelligence for Personalized Residential Interior Design Solutions - G. A. Alamry; L. M. Elwakeel (Kurdish Studies, 2024)
From smart homes to intelligent workplaces, the integration of cutting-edge technologies and artificial intelligence (AI) has paved the way for innovative solutions that enhance comfort, convenience, and efficiency. In this era of digital transformation, the potential of user-centered smart environments for residential interior design remains a compelling area of research. This article explores the advanced research on the integration of user preferences and artificial intelligence to develop personalized residential interior design solutions. We delve into the existing landscape, identify research gaps, and outline the research objectives that drive the need for this study. The comprehensive methodology for this research involves conducting a literature review to identify key principles and challenges, interviewing experts for insights, conducting a user study to identify needs and preferences, developing a framework based on these findings, implementing AI-powered algorithms for personalization, assessing usability in a real-world setting, conducting a SWOT analysis, interviewing stakeholders for recommendations, and developing a roadmap for the adoption of user-centered smart environments. This study has identified key principles, considerations, and challenges in the design and development of smart environments that prioritize user needs and preferences. These principles emphasize the importance of user involvement, personalization, privacy, security, accessibility, and affordability in the creation of smart living spaces. Additionally, challenges such as technical complexity, the lack of standards, and the crucial aspect of user acceptance were highlighted. This research sets the stage for future endeavors aimed at enhancing the quality of life within smart homes, while also addressing ethical concerns and promoting user satisfaction.